(untitled) (INTELLIGENCE Journal of Multidisciplinary Research, 2023)
This paper aims to examine the effect of the existence of joint venture (JV) banks on the performance of non-joint venture (NJV) commercial banks of Nepal. The study is based on secondary data, where the data have been collected from fourteen sampled banks’ annual reports, Ministry of Finance publications, and World Bank publications. Seven years of data from Fiscal Year 2013/14 to 2019/20 of cross-section units (banks) established before 2008 have been taken for the study. Descriptive analysis, correlation, and regression have been used in the study. The result depicts that JV banks’ existence in Nepal significantly impacts return on assets and credit risk levels but does not show an impact on the net interest margin (NIM) of NJV commercial banks. The regression result shows that loan deposit ratio, capital adequacy ratio (CAR), bank’s equity level, and non-performing loan (NPL) of JV banks substantially impact the NIM of NJV banks. Likewise, the interest spread rate and NPL of JV banks significantly affect the ROA of NJV commercial banks. Similarly, interest spread, CAR, and foreign ownership ratio significantly impact the credit risk level of NJV commercial banks in Nepal. Likewise, the result further shows that JV banks have been earning relatively higher non-interest income, which positively reflected on the ROA of banks. Additionally, JV banks have been booking low-quality credit portfolios at a lower interest rate.